2000
DOI: 10.1080/146608299300079493
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of visual search behaviour in ALS patients detected with event-related brain potentials

Abstract: A number of recent reports have emphasized neuropyschological symptoms in ALS, including frontal functions, memory and attention. We investigated visual search behaviour of ALS in two types of tasks: a simple, relatively effortless parallel search task and a more complex attention-demanding serial search task. Behavioural parameters and cognitive event-related potentials (ERP) from 19 scalp channels were obtained from 13 ALS patients and 13 matched controls during task performance. ALS patients showed the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Previous study by detecting spontaneous low-frequency fluctuations (LFF) of blood oxygen level–dependent signals of rfMRI showed decreased ALFF in the visual processing areas: the inferior occipital lobe and fusiform gyri (Luo et al, 2012 ). This result and our findings suggest a disorder of visual process, which is in accordance with previous task-related fMRI studies (Lulé et al, 2007 ; Wang et al, 2013 ) and electrophysiological studies(Münte et al, 1998 , 1999 ). A delayed and decreased response to visual stimuli was observed in sensory processing cortical areas in ALS patients by electrophysiological studies (Münte et al, 1998 , 1999 ), and a previous longitudinal study identified progressive reduced activation of extrastriate regions over the duration of ALS (Lulé et al, 2007 ).…”
Section: Discussionsupporting
confidence: 94%
“…Previous study by detecting spontaneous low-frequency fluctuations (LFF) of blood oxygen level–dependent signals of rfMRI showed decreased ALFF in the visual processing areas: the inferior occipital lobe and fusiform gyri (Luo et al, 2012 ). This result and our findings suggest a disorder of visual process, which is in accordance with previous task-related fMRI studies (Lulé et al, 2007 ; Wang et al, 2013 ) and electrophysiological studies(Münte et al, 1998 , 1999 ). A delayed and decreased response to visual stimuli was observed in sensory processing cortical areas in ALS patients by electrophysiological studies (Münte et al, 1998 , 1999 ), and a previous longitudinal study identified progressive reduced activation of extrastriate regions over the duration of ALS (Lulé et al, 2007 ).…”
Section: Discussionsupporting
confidence: 94%
“…This finding suggests a disturbance of visual process, which is in accordance with previous electrophysiological studies and task-related fMRI studies. A reduced and delayed response to visual stimuli was observed in sensory cortical processing areas in ALS patients by electrophysiological studies [64], [65], and progressive reduced activation of extrastriate areas over the course of ALS was identified by a previous longitudinal study [66]. Combining fMRI with structural MRI, researchers demonstrated the existence of a decreased response in secondary visual areas in ALS during visual stimulation, and significantly less functional white fiber tracts projecting to visual areas [67].…”
Section: Discussionmentioning
confidence: 95%
“…ALS is a neurodegenerative disease which involves mainly the motor system, but already early descriptions [70] and more recent neuropsychological [7174], electrophysiological [7577], neuropathological [14], and neuroimaging [7880] studies pointed out that other than the motor regions of the nervous system are involved in the degenerative process. …”
Section: Functional Magnetic Resonance Imagingmentioning
confidence: 99%